The seasonal reproduction number of dengue fever impacts of climate on transmission - Polwiang, Sittisede (PeerJ PrePrints, 2014)
Background: Dengue fever is mosquito-borne viral disease and regular epidemic in Thailand. The peak dengue epidemic period is around June to August during rain season. It is believed that climate plays an important role for dengue transmission. Method: Mathematical model for vector-host infectious disease was used to calculate the impacts of climate to the transmission of dengue virus. In this study, the data of climate and dengue fever cases were from Chiang Mai 2004-2013, Thailand. The value of seasonal reproduction number was calculated to evaluate the potential, severity and persistence of dengue infection. Results: The population of mosquito was increasing exponentially from the start of rain season in early May and reaches the peak in late June. The simulations suggest that the greatest potential of dengue transmission occurs at temperature equal to 28.7 ºC. The seasonal reproduction numbers was 0.62-3.05, above unity from February to November and reaches the peak in July. Discussion and Conclusion: The results have shown that dengue infection is depending on seasonal variation. The rainfall provides places for mosquito to laid eggs and develop to adult stage. Temperature plays an important role to mosquito life cycle and also mosquito behaviors. The seasonal reproduction number was corresponding to dengue incidences number and could measure the dengue transmission potential. The sensitive analysis suggested that avoiding or reducing contact with mosquito is the best method to reduce the dengue transmission.
Keywords: Dengue; Reproduction Number; Mathematical Model